ANALISIS PEMILIHAN KEPALA DAERAH CALON TUNGGAL PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 100/ PUU-XIII / 2015 (STUDI KASUS DI PROVINSI SULAWESI SELATAN) - Karim, Rahmawati; Mas, Marwan; Hamid, Abdul Haris (Postgraduate Bosowa University Publishing, 2019)
This study aims to determine the regulation of a single Regional Election for Regional Head Election simultaneously after the decision of the Constitutional Court Number 100 / PUU-XIII / 2015 in South Sulawesi Province, and the implementation of the selection of a single regional head candidate in South Sulawesi Province. This research was conducted in the Makassar City KPU, Enrekang Regency and Bone Regency. The research method used is normative law. The results obtained by the author from this study, namely 1). Regulation of the Single Candidate for Regional Head Election Simultaneously regulated in the Constitutional Court Decision Number 100 / PUU-XIII / 2015, Law no. 10 of 2016 and PKPU No. 13 of 2018.2). Implementation of Election of Candidates for Regional Heads in the Province of South Sulawesi consisting of; a). Requirements for Nominating a Single Candidate, b). Single Candidate Selection Dispute Process, c). Regulatory Standard for Inauguration of Single Candidate Candidates and, d). Single Candidate Selection Results in South Sulawesi Province.3). Mechanisms to Prevent the Occurrence of a Single Candidate in the Election of Regional Heads.4). Data on Candidates for Regional Heads in 3 regions, namely Makassar City, Enrekang Regency and Bone Regency.